Digital collection for blind and visually impaired people - Badurina, Boris; Dragija Ivanović, Martina; Gabriel, Dunja-Marija Golub, Koraljka; Lazić, Nikolaj Ravnić, Robert (2001)
The digital collection has been created to the purpose of ensuring better access to information for the blind and visually impaired. New technologies enable quick and simple access to information for this group of information users which had been so far restricted to slow and expensive process of material preparation (Braille texts, audio books, large print). Speech synthesis enables the blind to surf the World Wide Web and reach the information just as people who can see do. In order to make Internet retrieval efficient for all user categories (world statistics state that between 10% and 20% of population are people with different special needs), W3C Consortium has created guidelines (http://www.w3c.org/WAI/Resources) about ways in which web pages can be made accessible for all.
Projekt MZOS
ENG